Penerapan Digitalisasi pada Koperasi Budi Utomo Desa Batu Ampar - Agustian Noor; Muhammad Noor; Kurniasari - - (Joutica, 2022)
Budi Utomo's Savings and Loans Cooperative is one of the cooperatives in Indonesia that has not made optimal use of information systems and technology. It can be seen from the absence of an integrated information system with one another, so that there are still several obstacles in processing cooperative data, including inconsistencies and data redundancies, lack of data accuracy, the length of the data search process, and the difficulty of disseminating information about cooperatives to members. To solve this problem, we need a web-based Cooperative information system. This cooperative information system is designed using the PHP programming language and to describe the results of analysis and system design, structured modeling techniques are used in the form of DFD and ERD. The output of this research is a web-based information system prototype design (case study: Budi Utomo Savings and Loan Cooperative). With this cooperative information system, it is hoped that it can provide a forum in the form of a web that can perform data processing properly and is integrated, and can help disseminate information to all interested parties.